Growth motor development levels of young children in cricket, volleyball and athletics - Abdullah, Borhannudin; Shafie, Nor Amalina; Yusof, Aminuddin; Shamsudin, Shamsulariffin; Salehhodin, Siti Nur Sarah (Human Resource Management Academic Research Society, 2017)
The purpose of this study was to identify the gross motor development level of primary school students playing three different sports (athletics, volleyball and cricket). A total of 90 subjects (athletics = 30, volleyball=30, cricket =30) participated in the study. Gross motor development tests Ulrich (2000) with a coefficient of 0.88-0.96 (Hardy, 2009) was conducted to assess the level of gross motor development of young athletes from different sports. There was a significant difference [F (2,87) = 108.2, p = 0.00 ] for gross motor development among young athletes for different sports (athletics, crickets, and volleyball). Post hoc analysis on the GMDQ mean scores showed cricket and volleyball players differed from athletics (p<0.01). Age of locomotor (AEL) scores for the three types of sports also shows significant differences [F (2,87)=86.6, p<0.00] for all three sports. For control object scores (AEM), there were significant differences [F (2,87) = 61.2 , p = 0.00 ] between volleyball and cricket (p <0.01) players. There are differences in gross motor development among young children participating in sports such as athletics, volleyball, and cricket.